2013
DOI: 10.1111/nph.12221
|View full text |Cite
|
Sign up to set email alerts
|

The mycorrhizal‐associated nutrient economy: a new framework for predicting carbon–nutrient couplings in temperate forests

Abstract: SummaryUnderstanding the context dependence of ecosystem responses to global changes requires the development of new conceptual frameworks. Here we propose a framework for considering how tree species and their mycorrhizal associates differentially couple carbon (C) and nutrient cycles in temperate forests. Given that tree species predominantly associate with a single type of mycorrhizal fungi (arbuscular mycorrhizal (AM) fungi or ectomycorrhizal (ECM) fungi), and that the two types of fungi differ in their mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

57
978
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 840 publications
(1,041 citation statements)
references
References 130 publications
57
978
5
1
Order By: Relevance
“…We are also aware that the establishment of ECM plants in late‐successional dune systems is accompanied with a steep decline in pH (Read, 1989). Other examples relate to the faster decomposition of AM‐tree‐derived litter (Cornelissen, Aerts, Cerabolini, Werger, & van der Heijden, 2001) and N and P cycling rates (Phillips et al., 2013). Despite controlling for the abovementioned factors, ours was still an observational study for which causality cannot be directly shown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We are also aware that the establishment of ECM plants in late‐successional dune systems is accompanied with a steep decline in pH (Read, 1989). Other examples relate to the faster decomposition of AM‐tree‐derived litter (Cornelissen, Aerts, Cerabolini, Werger, & van der Heijden, 2001) and N and P cycling rates (Phillips et al., 2013). Despite controlling for the abovementioned factors, ours was still an observational study for which causality cannot be directly shown.…”
Section: Discussionmentioning
confidence: 99%
“…We also do not think that this pattern is caused by production of enzymes that facilitate AM establishment by AM woody plants, as there is no evidence that any AM‐specific enzymes exist. We suggest that in part the relationship we observe is due to AM‐colonized trees speeding up nutrient cycling (Phillips et al., 2013) which enables establishment of herbaceous plants that associate with AM. This (biotic) effect may be present even after accounting for observed differences in abiotic parameters and could explain the relationship between relative richness of AM herbaceous plants and that of relative abundance of AM woody species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this mutualism, the fungus transfers nutrients and water to the plant in exchange for carbohydrates, necessary for fungal growth. Mycorrhizal fungi are critical for terrestrial C cycling (17), are known to influence plant growth (18), nutrient cycling (19,20), and soil carbon storage (21), and respond strongly to elevated CO 2 (22,23). Yet, their impact on the N-dependence of the CO 2 fertilization effect has not been tested, despite the increasing evidence that N limitation constrains the CO 2 fertilization effect (5).…”
mentioning
confidence: 99%
“…ECM can transfer N to the host plant under eCO 2 to sustain CO 2 fertilization (25), whereas the symbiotic effects of AM fungi in N-limited systems can range from beneficial to parasitic (19). Hence, the association of Liquidambar styraciflua with AM-fungi at ORNL, and Pinus taeda with ECM-fungi at Duke, might explain why only trees in the latter could increase N-uptake and take advantage of eCO 2 to grow faster for a sustained period (20,25). Here, we tested the hypothesis that the differences in the nutrient economies of ECM and AM fungi influence global patterns of the magnitude of plant biomass responses to elevated CO 2 .…”
mentioning
confidence: 99%